Covid-19, Flexible Working, and Implications for Gender Equality in the United Kingdom. Issue 2 (April 2021) - Chung, Heejung; Birkett, Holly; Forbes, Sarah; Seo, Hyojin
We examine the role flexible working has for gender equality during the pandemic, focusing on arrangements that give workers control over when and where they work. We use a survey of dual-earning working parents in the United Kingdom during the peak of the first lockdown, namely, between mid-May and mid-June 2020. Results show that in most households in our survey, mothers were mainly responsible for housework and child care tasks both before and during the lockdown period, although this proportion has slightly declined during the pandemic. In households where fathers worked from home during the pandemic, respondents were less likely to say that mothers were the ones solely or mostly responsible for housework and child care. Fathers who worked from home were more likely to say that they were doing more housework and child care during the lockdown period than they were before. Finally, we explore what we expect to happen in the postpandemic times in relation to flexible working and gender equality. The large expansion of flexible working we expect to happen may help reduce some of the gender inequalities that have exacerbated during the pandemic, but only if we reflect on and change our existing work cultures and gender norms.